A phase II randomized, multicenter, open-label trial of continuing adjuvant temozolomide beyond 6 cycles in patients with glioblastoma (GEINO 14-01). Issue 12 (24th April 2020) - Balana, Carmen; Vaz, Maria Angeles; Manuel Sepúlveda, Juan; Mesia, Carlos; del Barco, Sonia; Pineda, Estela; Muñoz-Langa, Jose; Estival, Anna; de las Peñas, Ramón; Fuster, Jose; Gironés, Regina; Navarro, Luis Miguel; et al.
Abstract: Background: Standard treatment for glioblastoma is radiation with concomitant and adjuvant temozolomide for 6 cycles, although the optimal number of cycles of adjuvant temozolomide has long been a subject of debate. We performed a phase II randomized trial investigating whether extending adjuvant temozolomide for more than 6 cycles improved outcome. Methods: Glioblastoma patients treated at 20 Spanish hospitals who had not progressed after 6 cycles of adjuvant temozolomide were centrally randomized to stop (control arm) or continue (experimental arm) temozolomide up to a total of 12 cycles at the same doses they were receiving in cycle 6. Patients were stratified by MGMT methylation and measurable disease. The primary endpoint was differences in 6-month progression-free survival (PFS). Secondary endpoints were PFS, overall survival (OS), and safety (Clinicaltrials.gov NCT02209948). Results: From August 2014 to November 2018, 166 patients were screened, 7 of whom were ineligible. Seventy-nine patients were included in the stop arm and 80 in the experimental arm. All patients were included in the analyses of outcomes and of safety. There were no differences in 6-month PFS (control 55.7%; experimental 61.3%), PFS, or OS between arms. MGMT methylation and absence of measurable disease were independent factors of better outcome. Patients in the experimental arm had more lymphopenia ( P  < 0.001), thrombocytopenia ( P  < 0.001), and nausea and vomiting ( P  = 0.001). Conclusions: Continuing temozolomide after 6 adjuvant cycles is associated with greater toxicity but confers no additional benefit in 6-month PFS. Key Points: 1. Extending adjuvant temozolomide to 12 cycles did not improve 6-month PFS. 2. Extending adjuvant temozolomide did not improve PFS or OS in any patient subset. 3. Extending adjuvant temozolomide was linked to increased toxicities.